The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.18488/journal.61.2018.64.227.238
|View full text |Cite
|
Sign up to set email alerts
|

Metadiscourse in the Academic Writing of Local and International Students at a University in Malaysia

Abstract: Article HistoryKeywords Academic writing Interactive markers Interactional markers Metadiscourse markers Textual analysis Malaysia.This study examines the use of metadiscourse markers among 50 Malaysian and 50 Arab Pre-University students. The findings of this study indicated that there was a significant difference in the use of metadiscourse markers between Malaysian and Arab Pre-University students {χ2 (1, n = 100) = 7.17, p-value is .007} where the use of metadiscourse markers among Malaysian Pre-Universit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…6 In terms of Arabic-English contrastive studies, 7 study is particularly interesting, as it compares the use of validity markers and attitude markers in English and Arabic argumentative writing, comparing the use of these two categories of metadiscourse in native English and native Arabic student's argumentative essays, 8 Despite metadiscourse categories fluctuate in frequency and preferred forms 9 These categories typically emerge in the same situations to engage with texts in both native Arabic and native English, as well as across L1-L2 texts in each language, demonstrating their level of commitment to the text and attitude towards each other. 10 To compare and contrast the signs of interactive and interactional metadiscourse in 60 linguistics research papers (RAs) written in both languages. 11 He found that linguistic RAs in both English and Arabic place a lot of emphasis on metadiscourse markers.…”
Section: Introductionmentioning
confidence: 99%
“…6 In terms of Arabic-English contrastive studies, 7 study is particularly interesting, as it compares the use of validity markers and attitude markers in English and Arabic argumentative writing, comparing the use of these two categories of metadiscourse in native English and native Arabic student's argumentative essays, 8 Despite metadiscourse categories fluctuate in frequency and preferred forms 9 These categories typically emerge in the same situations to engage with texts in both native Arabic and native English, as well as across L1-L2 texts in each language, demonstrating their level of commitment to the text and attitude towards each other. 10 To compare and contrast the signs of interactive and interactional metadiscourse in 60 linguistics research papers (RAs) written in both languages. 11 He found that linguistic RAs in both English and Arabic place a lot of emphasis on metadiscourse markers.…”
Section: Introductionmentioning
confidence: 99%